Design of 32-Bit Arithmetic Logic Unit Using Shannon Theorem Based Adder Approach - C., Senthilpari (2009)
This thesis proposes two new techniques for the design of full adder circuits namely, Mixed-Shannon and Shannon circuits. The Mixed-Shannon adder cell is developed using the MCIT for the sum operation and the Shannon based technique for the carry. In the second technique approach, the full adder circuit is designed completely by using the Shannon theorem. The Mixed-Shannon and full Shannon adder cells are used in the implementation of 8-bit array multipliers, namely, the Braun array, CSM and Baugh-Wooley multipliers. Output parameters such as propagation delay, total chip area, and power dissipation are calculated from the simulation results.